MODEL KONSEP TEORI KEPERAWATAN HILDEGARD ELIZABETH PEPLAU DENGAN SKIZOFRENIA - Istinganah; Irna Nursanti (Nusantara Hasana Journal, 2024)
This paper aims to describe the application of Hildegard Elizabeth Peplau's nursing theory concept model in caring for individuals with schizophrenia. This theory emphasizes the interpersonal relationship between nurses and patients as a key factor in the healing process. In the context of schizophrenia, this relationship becomes more complex due to the characteristics of the symptoms and communication challenges. Nurses serve as "counselors" who help patients understand and manage their psychotic experiences. The process of identifying and managing feelings becomes the main focus, with nurses guiding patients to develop adaptation skills. In addition, nurses also act as mediators between patients and their environment, helping to facilitate social integration. Hildegard Elizabeth Peplau's conceptual model of nursing theory can be a valuable guide in caring for individuals with schizophrenia. Application of its interpersonal principles can help strengthen relationships between nurses and patients, provide necessary support for the healing process, and improve the quality of care for individuals with schizophrenic disorders.